2014
DOI: 10.15381/rivep.v25i4.10782
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de Cuatro Tiempos de Cultivo sobre la Tasa de Maduración y División Post-Fecundación in vitro de Ovocitos de Alpaca

Abstract: RESUMENSe evaluó el efecto del tiempo de cultivo sobre la tasa de maduración nuclear y tasa de división posfecundación a 72 horas de ovocitos de alpacas. Complejos CumulusOvocitos (CCOs) fueron obtenidos de ovarios procedentes de animales beneficiados en el camal y transportados a 35 °C en solución salina 0.9% suplementada con antibiótico antimicótico. Los CCOs fueron aspirados de folículos de 2 a 6 mm. Experimento 1: 502 ovocitos fueron distribuidos en cuatro tiempos de maduración (30, 34, 38 y 42 horas) y ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
2
6
0
6
Order By: Relevance
“…Likewise, the percentages of GVBD were similar to previous studies in llamas (Sansinena et al 2003), but they differ from other reports in alpacas (Ratto et al 2005;Ratto et al 2007;Ruiz et al 2017) and dromedary camels (Farag et al 2013). The percentages of DG were similar to previous reports for alpacas (Ratto et al 2007;Ruiz et al 2017) and dromedary camels (Farag et al 2013), but they are higher than other reports in alpacas (Huanca et al 2014) and llamas (Ratto et al 2005). The percentages of GV found in this study are in agreement with the results reported for alpacas (Huanca et al 2014;Ruiz et al 2017) and dromedary camels (Farag et al 2013).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Likewise, the percentages of GVBD were similar to previous studies in llamas (Sansinena et al 2003), but they differ from other reports in alpacas (Ratto et al 2005;Ratto et al 2007;Ruiz et al 2017) and dromedary camels (Farag et al 2013). The percentages of DG were similar to previous reports for alpacas (Ratto et al 2007;Ruiz et al 2017) and dromedary camels (Farag et al 2013), but they are higher than other reports in alpacas (Huanca et al 2014) and llamas (Ratto et al 2005). The percentages of GV found in this study are in agreement with the results reported for alpacas (Huanca et al 2014;Ruiz et al 2017) and dromedary camels (Farag et al 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies using higher concentrations of FSH (0.5μg.mL -1 ) allowed similar maturation rates, such as 5μg.mL -1 of FSH in llamas (Sansinena et al 2003); 10 µg.mL -1 of b-FSH and b-LH in dromedary camels (Nowshari, 2005). However, other studies have shown higher rates of maturation of oocytes when using 0.5µg.mL -1 of FSH in alpacas (Ratto et al 2007;Huanca et al 2014;Ruiz et al 2017) and llamas (Ratto et al 2005). However, the same concentration of FSH, 0.5μg.mL -1 , has resulted in lower rates of maturation in llamas (Del Campo et al 1994).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…As an alternative to AI, embryo transfer has been attempted in SACs (10). Successful within-species embryo transfer was achieved in both llamas (11)(12)(13)(14) and alpacas (15,16). Crossspecies embryo transfer between SACs was also accomplished with in vivo generated embryos (12,17,18).…”
Section: Introductionmentioning
confidence: 99%